A kind of ultra-high strength repairable and recyclable elastomeric material and preparation method thereof
Through the chemical copolymerization of conjugated polymer A and linear polymer B, an ultra-high strength elastomer material was prepared, which solved the problem of the inability to repair and recycling of existing materials, and achieved high strength and excellent material Repair and recycling performance.
Patent Information
- Application Number
- CN202310157609.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-23
AI Technical Summary
Existing high-performance elastomeric materials cannot be repaired and recycled, resulting in waste of resources and environmental pollution, and the strength of materials enhanced by nano-microstructures is still limited.
Through the chemical copolymerization of conjugated polymer A and linear polymer B, an ultra-high strength elastomer material is formed. Conjugated polymer A provides a rigid framework as a hard segment and realizes self-assembly in the polymer network to form a nanomicrophase region. Linear polymer B contains hydrogen bonds, which can effectively dissipate energy during the stretching process and improve the tensile properties of the elastomer.
The ultra-high strength, excellent mechanical properties, and good repair and recycling performance of elastomeric materials are achieved, which reduces material maintenance costs and avoids waste of resources and environmental pollution.
Smart Images

Figure CN116102704B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-performance elastomeric materials, and in particular to an ultra-high-strength repairable and recyclable elastomeric material and a preparation method thereof. Background Art
[0002] Elastomer materials are widely used in many fields of life due to their excellent mechanical properties, such as automobiles, flexible devices, and medical fields. However, current high-performance elastomer materials are generally achieved through permanent cross-linking, which cannot achieve the function of repair or recycling, thus causing a large amount of resource waste and environmental pollution. With the progress of the times, it is very necessary to give elastomer materials the ability to repair and recycle.
[0003] Nowadays, the function of repairing and recycling elastomeric materials is generally achieved through reversible crosslinking. However, reversibly crosslinked elastomeric materials generally cause a decrease in mechanical properties, making it difficult to achieve application in practical fields. In recent years, introducing nanostructures into elastomeric materials is an effective way to enhance elastomers. At the same time, this method is easier to achieve material repair and recycling than permanent crosslinking. However, the elastomeric materials prepared by nanostructure enhancement are still limited in strength. Therefore, it is still difficult to prepare elastomeric materials that have excellent mechanical properties and can be repaired and recycled. Summary of the invention
[0004] The object of the present invention is to provide an ultra-high strength repairable and recyclable elastomeric material and a preparation method thereof. The elastomeric material provided by the present invention also has excellent mechanical properties and can be repaired and recycled.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an elastomeric material, which is copolymerized by a conjugated polymer A and a linear polymer B; the molar amount of the conjugated polymer A is 25-50% of the total molar amount of the conjugated polymer A and the linear polymer B;
[0007] The conjugated polymer A is an amino- or hydroxy-terminated conjugated polymer;
[0008] The linear polymer B is a linear polymer containing hydrogen bonds and isocyanate groups.
[0009] Preferably, the conjugated polymer A is one or more of amino-terminated polyimide, hydroxy-terminated polyimide, amino-terminated polyetheretherketone, hydroxy-terminated polyetheretherketone, amino-terminated polyetherimide and hydroxy-terminated polyetherimide.
[0010] Preferably, the linear polymer B is one or more of isocyanate-terminated polyurethane, polyurea and polyureaurethane.
[0011] The present invention provides a method for preparing the elastomeric material described in the above scheme, comprising the following steps: dissolving a conjugated polymer A and a linear polymer B in an organic solvent, performing a copolymerization reaction, and removing the organic solvent to obtain the elastomeric material.
[0012] Preferably, the copolymerization reaction temperature is 60-80°C.
[0013] Preferably, the copolymerization reaction time is 8 to 24 hours.
[0014] Preferably, the organic solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, acetonitrile, N-methylpyrrolidone and chloroform.
[0015] Preferably, the total concentration of the conjugated polymer A and the linear polymer B in the organic solvent is 40-100 mg / mL.
[0016] Preferably, the removing of the organic solvent comprises: placing the polymer solution obtained by the copolymerization reaction at 25-90° C. to volatilize the organic solvent.
[0017] Preferably, the copolymerization reaction is carried out in the presence of a catalyst.
[0018] The present invention provides an elastomeric material, which is copolymerized by a conjugated polymer A and a linear polymer B; the molar amount of the conjugated polymer A is 25-50% of the total molar amount of the conjugated polymer A and the linear polymer B; the conjugated polymer A is an amino- or hydroxyl-terminated conjugated polymer; and the linear polymer B is a linear polymer containing hydrogen bonds and isocyanate groups.
[0019] The principle of the present invention is as follows: conjugated polymer A and linear polymer B react with isocyanate groups through amino groups (or hydroxyl groups) to achieve copolymerization. They play different roles in elastomers: conjugated polymer A acts as a hard segment to provide a rigid skeleton for the elastomer; conjugated polymer A can achieve self-assembly in the polymer network to form a nano-microphase region, further enhancing the elastomer material. The linear polymer B contains a large number of hydrogen bonds, which can achieve effective energy dissipation during the stretching process, thereby improving the tensile properties of the elastomer. The present invention combines the two polymers together by chemical copolymerization, and the material does not show an obvious phase separation structure on a macro scale. Since no permanent cross-linking sites are introduced into the elastomer material, the functions of repair and recycling can be achieved.
[0020] When the elastomeric material of the present invention is damaged, the wound is soaked in a suitable solvent, and then heated to volatilize the solvent, so that the material can be repaired. The used elastomeric material can be hot-pressed and recovered under a certain pressure and temperature. The used elastomeric material is dissolved in an organic solvent, and the elastomeric material can also be recycled. Whether it is the mechanical properties after repair or recycling, its strength is almost the same as that of the raw materials, showing its excellent repair and recycling performance. The present invention greatly reduces the maintenance cost of the elastomeric material and avoids the waste of materials and environmental pollution. In addition, since the prepared elastomer exhibits extremely excellent mechanical properties, the elastomeric material in the present invention also exhibits excellent scratch resistance and puncture resistance.
[0021] The synthesis process of the elastomeric material of the present invention is simple, and large-area preparation of the material can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The figure shows the elastic material and the tensile curve of Example 1 of the present invention;
[0023] Figure 2 is a tensile curve diagram of the repaired elastomeric material of Example 2 of the present invention;
[0024] Figure 3 is a tensile curve diagram of the recycled elastomer material of Example 2 of the present invention;
[0025] Figure 4 The anti-scratch photograph of the elastomeric material of Example 3 of the present invention and the corresponding scanning electron microscope image;
[0026] Figure 5 This is a diagram showing the puncture resistance of the elastomeric material of Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The present invention provides an elastomeric material, which is copolymerized by a conjugated polymer A and a linear polymer B; the molar amount of the conjugated polymer A is 25-50% of the total molar amount of the conjugated polymer A and the linear polymer B;
[0028] The conjugated polymer A is an amino- or hydroxy-terminated conjugated polymer;
[0029] The linear polymer B is a linear polymer containing hydrogen bonds and isocyanate groups.
[0030] In the present invention, the conjugated polymer A is preferably one or more of amino-terminated polyimide, hydroxy-terminated polyimide, amino-terminated polyetheretherketone, hydroxy-terminated polyetheretherketone, amino-terminated polyetherimide and hydroxy-terminated polyetherimide.
[0031] In the present invention, the linear polymer B is preferably one or more of isocyanate-terminated polyurethane, polyurea and polyureaurethane.
[0032] The present invention has no special requirements on the sources of the conjugated polymer A and the linear polymer B, and they can be prepared using commercial products well known in the art or methods well known in the art.
[0033] In the present invention, the molar amount of the conjugated polymer A is preferably 30-45% of the total molar amount of the conjugated polymer A and the linear polymer B, and more preferably 35-40%.
[0034] In the present invention, conjugated polymer A acts as a hard segment to provide a rigid skeleton for the elastomer, and conjugated polymer A can realize self-assembly in the polymer network to form a nano-microphase region, further enhancing the elastomeric material. The linear polymer B contains a large number of hydrogen bonds, which can achieve effective energy dissipation during the stretching process, thereby improving the tensile properties of the elastomer. The present invention combines the two polymers together by chemical copolymerization, and the material does not show an obvious phase separation structure in the macroscopic view. Since no permanent cross-linking sites are introduced into the elastomeric material, the functions of repair and recycling can be realized.
[0035] The present invention provides a method for preparing the elastomeric material described in the above scheme, comprising the following steps: dissolving a conjugated polymer A and a linear polymer B in an organic solvent, performing a copolymerization reaction, and removing the organic solvent to obtain the elastomeric material.
[0036] In the present invention, the organic solvent preferably includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, acetonitrile, N-methylpyrrolidone and chloroform.
[0037] In the present invention, the total concentration of the conjugated polymer A and the linear polymer B in the organic solvent is preferably 40-100 mg / mL, and in the embodiments of the present invention, specifically 50 mg / mL or 60 mg / mL.
[0038] The present invention has no special requirements for the dissolution process, and any dissolution process known in the art may be used.
[0039] In the present invention, the copolymerization reaction temperature is preferably 60 to 80° C., more preferably 70 to 80° C.; the reaction time is preferably 8 to 24 h, more preferably 12 to 20 h, and further preferably 24 h.
[0040] In the present invention, the copolymerization reaction is preferably carried out in the presence of a catalyst. The present invention has no special requirements on the specific type and amount of the catalyst. The catalyst and conventional amount used for the copolymerization reaction of amino (or hydroxyl) and isocyanate groups well known in the art can be used. In an embodiment of the present invention, the catalyst is specifically a dibutyltin dilaurate catalyst.
[0041] In the present invention, the conjugated polymer A and the linear polymer B are preferably dissolved in an organic solvent, the obtained solution is heated to a copolymerization temperature, and then a catalyst is added to carry out a copolymerization reaction.
[0042] In the present invention, the copolymerization reaction is preferably carried out under stirring conditions. The present invention has no particular limitation on the stirring speed, and the stirring speed of the copolymerization reaction well known to those skilled in the art can be used. In the copolymerization reaction process of the present invention, the amino group or hydroxyl group in the conjugated polymer A reacts with the isocyanate group in the linear polymer B to achieve copolymerization.
[0043] After the copolymerization reaction is completed, the present invention removes the organic solvent in the obtained polymer solution to obtain the elastomeric material.
[0044] In the present invention, the removal of the organic solvent preferably comprises: placing the polymer solution at 25 to 90° C. to volatilize the organic solvent. The present invention can further select a suitable temperature within the above range according to the type of solvent. The present invention preferably pours the polymer solution into a glass culture dish or a polytetrafluoroethylene mold, and then places the culture dish or mold containing the polymer solution in an oven to remove the organic solvent.
[0045] When the elastomeric material of the present invention is damaged, the wound is soaked in a suitable solvent for a certain period of time, and then heated to volatilize the solvent, so that the material can be repaired. In the present invention, the solvent used for the repair is preferably one or more of N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, acetonitrile, N-methylpyrrolidone and chloroform; in the present invention, the soaking time depends on the sample size and the selected repair solvent; the heating temperature depends on the repair solvent.
[0046] When the elastomeric material of the present invention is to be recycled, the used elastomeric material can be hot-pressed and recovered at a certain pressure and temperature. In the present invention, the hot-pressing temperature is 150-230° C. and the pressure is 2-5 MPa.
[0047] Alternatively, the used elastomer material can be dissolved in an organic solvent, and the elastomer material can also be recycled. The concentration of the polymer solution after dissolution is preferably 100-200 mg / mL.
[0048] The ultra-high strength repairable and recyclable elastomeric material and its preparation method provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0049] Example 1
[0050] A method for preparing an ultra-high strength repairable and recyclable elastomer, wherein the amount of each raw material is calculated by mole fraction as follows:
[0051] 1) amino-terminated polyetheretherketone 25%; 2) self-made isocyanate-terminated polyurethane, 75%.
[0052] The preparation process of the homemade isocyanate-terminated polyurethane is as follows: dissolve hydroxyl-terminated polytetrahydrofuran with a molecular weight of 2000 in dry tetrahydrofuran solvent at a concentration of 200 mg / mL, add an excess of dicyclohexylmethane-4,4'-diisocyanate, heat to 60°C, add three drops of dibutyltin dilaurate, and then continue the reaction at this temperature for 3 hours to obtain the isocyanate-terminated polyurethane.
[0053] Amino-terminated polyetheretherketone and isocyanate-terminated polyurethane were dissolved in N,N-dimethylformamide at a concentration of 60 mg / mL, then heated to 85°C, three drops of dibutyltin dilaurate catalyst were added, and stirring was continued for 3 days until the reaction was completed to obtain a light yellow polymer solution. The solution was poured into a glass watch glass, and then the watch glass was placed in an oven at 50°C to evaporate the solvent. After 24 hours, the solvent evaporated completely to obtain a complete elastic film.
[0054] After testing with a universal material testing machine, the elastomer material strength was found to be 128MPa and the toughness was 379MJ·m -3 ( Figure 1 ), which is an ultra-high performance elastomer material. Subsequently, the material was cut in the middle, the fracture was soaked in N,N-dimethylformamide for 20 seconds, and then placed in an oven at 50°C to dry the solvent, so that the elastomer could be repaired. Through tensile testing, it can be found that the strength of the repaired elastomer is 125MPa and the toughness is 358MJ·m -3 The tensile properties are almost consistent with the material before repair, demonstrating its good repair performance.
[0055] After the elastomeric material is chopped up, it can be redissolved in N,N-dimethylacetamide and placed back in the mold for film laying to obtain a new elastomeric film. In addition, the chopped elastomeric material can be placed in a hot press at a pressure of 4MPa and a temperature of 220°C to achieve material recycling. Using the above two recycling methods, the obtained material was recycled twice, and it was found that a complete film could still be obtained. The material after two cycles was tested using a universal material testing machine, and it was found that its mechanical properties had hardly changed. The specific results are shown in Table 1. This shows that the material has extremely excellent recycling performance. Since the prepared elastomer exhibits extremely excellent mechanical properties, the elastomeric material in the invention also exhibits excellent scratch resistance and puncture resistance.
[0056] Table 1 Recycling results of the elastomer material of Example 1
[0057]
[0058] Example 2
[0059] A method for preparing an ultra-high strength repairable and recyclable elastomer, wherein the amount of each raw material is calculated by mole fraction as follows:
[0060] 1) amino-terminated polyimide, 35%; 2) self-made isocyanate-terminated polyureaurethane, 65%.
[0061] The preparation process of the homemade isocyanate-terminated polyureaurethane is as follows: dissolve the hydroxyl-terminated polytetrahydrofuran with a molecular weight of 2000 in dry N,N-dimethylacetamide at a concentration of 200 mg / mL, add an excess of dicyclohexylmethane-4,4'-diisocyanate, and then add three drops of dibutyltin dilaurate after heating to 60°C. Then, continue the reaction at this temperature for 3 hours, then add isophthalic acid dihydrazine, and continue the reaction for 30 minutes to obtain the isocyanate-terminated polyureaurethane.
[0062] Amino-terminated polyimide and isocyanate-terminated polyureaurethane were dissolved in N,N-dimethylacetamide at a concentration of 50 mg / mL, then heated to 80°C, three drops of dibutyltin dilaurate catalyst were added, and stirring was continued for 3 days until the reaction was completed to obtain a light yellow polymer solution. The solution was poured into a glass watch glass, and then the watch glass was placed in an oven at 50°C to evaporate the solvent. After 24 hours, the solvent evaporated completely to obtain a complete elastic film.
[0063] After testing with a universal material testing machine, the elastomer material strength was found to be 142MPa and the toughness was 527MJ·m -3This is unprecedented in previous elastomers. The material was cut in the middle, and then the fracture was soaked in N,N-dimethylformamide for 20 seconds, and then placed in an oven at 50°C to dry the solvent, which can achieve the repair of the elastomer. Through tensile testing, it can be found that the tensile properties of the repaired elastomer are almost the same as those of the material before repair, showing its good repair performance ( Figure 2 ). After the elastomer material is chopped up, it can be dissolved in N,N-dimethylacetamide again and placed in the mold again to form a new elastomer film. In addition, the chopped elastomer material can also be placed in a hot press at a pressure of 4MPa and a temperature of 220°C to achieve material recycling. The material after three cycles was tested using a universal material testing machine and found that its mechanical properties had almost no change. The specific results are shown in Figure 3 , Figure 3 The corresponding data are shown in Table 2. Since the prepared elastomer exhibits extremely excellent mechanical properties, the elastomer material in the invention also exhibits excellent anti-scratch and anti-puncture properties.
[0064] Table 2 Recycling results of the elastomer material of Example 2
[0065]
[0066]
[0067] Example 3
[0068] A method for preparing an ultra-high strength repairable and recyclable elastomer, wherein the amount of each raw material is calculated by mole fraction as follows:
[0069] 1) 45% of hydroxyl-terminated polyetherimide; 2) 55% of isocyanate-terminated polyurea.
[0070] The preparation process of the homemade isocyanate-terminated polyurea is as follows: dissolve the amino-terminated polyethylene glycol with a molecular weight of 2000 in dry tetrahydrofuran solvent at a concentration of about 200 mg / mL, add an excess of dicyclohexylmethane-4,4'-diisocyanate, and continue the reaction at 60°C for 3 hours to obtain the isocyanate-terminated polyurea.
[0071] Hydroxyl-terminated polyetherimide and isocyanate-terminated polyurea were dissolved in dimethyl sulfoxide at a concentration of 60 mg / mL, then heated to 85°C, three drops of dibutyltin dilaurate catalyst were added, and stirring was continued for 3 days until the reaction was completed to obtain a light yellow polymer solution. The solution was poured into a glass watch glass, and the watch glass was placed in an oven at 50°C to evaporate the solvent. After 36 hours, the solvent evaporated completely to obtain a complete elastic film.
[0072] After testing with a universal material testing machine, the elastomer material strength was found to be 139 MPa and the toughness was 513 MJ·m -3 , which is an ultra-high performance elastomeric material. Since the prepared elastomer exhibits extremely excellent mechanical properties, the elastomeric material in the invention also exhibits excellent anti-scratch performance, and there is still no scratch after being scratched 2000 times ( Figure 4 The elastomeric material can move 19mm under puncture test conditions, showing excellent puncture resistance ( Figure 5 ). Subsequently, the material was cut in the middle, the fracture was immersed in N,N-dimethylformamide for 20s, and then placed in an oven at 50°C to dry the solvent, so that the repair of the elastomer could be achieved. Through the tensile test, it can be obtained that the tensile properties of the repaired elastomer are almost the same as those of the material before the repair, showing its good repair performance. After the elastomer material is chopped up, it can be redissolved in dimethyl sulfoxide and placed in the mold again for film laying to obtain a new elastomer film. In addition, the chopped elastomer material is placed in a hot press at a pressure of 4MPa and a temperature of 220°C, and the material can also be recycled. Using the above two recycling methods, the obtained material was recycled twice, and it was found that a complete film could still be obtained. The material after two cycles was tested using a universal material testing machine. The test results are shown in Table 3. It was found that its mechanical properties were almost unchanged, indicating that the material has extremely excellent recycling performance.
[0073] Table 3 Recycling results of the elastomer material of Example 3
[0074]
[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An elastomeric material, characterized in that: It is formed by copolymerization of a conjugated polymer A and a linear polymer B; the molar amount of the conjugated polymer A is 25 to 50% of the total molar amount of the conjugated polymer A and the linear polymer B; The conjugated polymer A is one or more of amino-terminated polyimide, hydroxy-terminated polyimide, amino-terminated polyetheretherketone, hydroxy-terminated polyetheretherketone, amino-terminated polyetherimide and hydroxy-terminated polyetherimide; The linear polymer B is one or more of isocyanate-terminated polyurethane, polyurea and polyureaurethane.
2. The method for preparing the elastomeric material according to claim 1, characterized in that: The following steps are involved: The conjugated polymer A and the linear polymer B are dissolved in an organic solvent to carry out copolymerization reaction, and the elastomeric material is obtained after removing the organic solvent.
3. The preparation method according to claim 2, characterized in that: The temperature of the copolymerization reaction is 60-80°C.
4. The preparation method according to claim 2 or 3, characterized in that: The copolymerization reaction time is 8 to 24 hours.
5. The preparation method according to claim 2, characterized in that: The organic solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, acetonitrile, N-methylpyrrolidone and chloroform.
6. The preparation method according to claim 2 or 5, characterized in that: The total concentration of the conjugated polymer A and the linear polymer B in the organic solvent is 40-100 mg / mL.
7. The preparation method according to claim 2 or 5, characterized in that: The removing of the organic solvent comprises: placing the polymer solution obtained by the copolymerization reaction at 25-90° C. to volatilize the organic solvent.
8. The preparation method according to claim 2 or 3, characterized in that: The copolymerization reaction is carried out in the presence of a catalyst.
Citation Information
Patent Citations
Polyurea-polyimide block copolymer molding powder and preparation method thereof
CN109942825A
High-toughness high-mechanical-strength polyurethane elastomer with recycling and self-repairing functions and preparation method thereof
CN110698635A